Enhancing urban water utilities: a case study of the Utility of the Future framework implementation in Indonesia - Yureana Wijayanti; Oki Setyandito (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska)
Utility companies worldwide face unique challenges in innovation, inclusivity, market focus, and resilience. A uniform approach to action plans is impractical. The Utility of the Future (UoF) framework aims to guide companies in developing tailored action plans that reflect their specific areas of focus and long-term objectives. Therefore, the objective of this paper is to elaborate on the implementation of the UoF approach in reviewing the utility’s performance and in developing the 100-day action plans. The case study is a local government-owned enterprise of the water utility, Perumda Tirta Musi, in Palembang City, South Sumatra, Indonesia. The outcome is a 100-day action plan with short-term steps and a five-year plan with long-term actions. It shows that the UoF methodology can help water utilities understand their current condition and gaps from the current benchmark to their future goals, enabling inclusive action plans for world-class water utilities. Future studies will explore further UoF implementations in Indonesia to provide insights into sustainable performance improvement strategies.